Writing Japanese Katakana : an Introductory Japanese Language Workbook. - Jim (Tuttle Publishing, 2013)
This is an introductory guide and workbook to writing Japanese Katakana. Anybody who is able to master English, with its irregular spellings and idiosyncratic pronunciations, is more than equipped to master written Japanese. The hiragana and katakana syllabaries are purely phonetic characters, which function much like the letters of the English alphabet. In this respect, kana are quite different from kanji characters, which are based on Chinese ideographs and which represent ideas. The katakana syllabary is used primarily to represent borrowed words (from languages other than Chinese), altho.